Artificial Intelligence in Personalized Learning: A New Era of Education - Faisal Tariq Hasan; Rafiq Rahman (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Artificial Intelligence (AI) is reshaping education by enabling personalized learning experiences tailored to individual students' needs. This paper examines the application of AI-driven systems in adaptive learning platforms, intelligent tutoring, and automated assessments. It highlights how AI enhances student engagement, provides real-time feedback, and improves learning outcomes. The study concludes that AI-driven education fosters better student performance and learning efficiency.